Sehgal-Guseman-Type Fixed Point Theorems in Rectangular b-Metric Spaces and Solvability of Nonlinear Integral Equation - Hongyan Guan; Chen Lang; Yan Hao (Journal of Function Spaces)
Firstly, the concept of a new triangular α-orbital admissible condition is introduced, and two fixed point theorems for Sehgal-Guseman-type mappings are investigated in the framework of rectangular b-metric spaces. Secondly, some examples are presented to illustrate the availability of our results. At the same time, we furnished the existence and uniqueness of solution of an integral equation.